Analysis of the Effect of Transformational Leadership and Innovative Behaviour on Employee Performance at PT Supra Primatama Nusantara - Rizqita Nurhajizah Lubis; Darmilisani Darmilisani; Akhmad Taufik (Journal of Research in Social Science and Humanities, 2025)
This research aims to find out the extent to which transformational leadership and innovative behavior simultaneously influence employee performance at PT Supra Primatama Nusantara (Biznet) Medan Branch. Quantitative research is research that uses data in the form of numbers as a tool to find information about what you want to know. Population in this study were all employees who worked at PT Supra Primatama Nusantara (Biznet) Medan Branch, totaling 120 people, the sample in this study was 55 respondents who were obtained using the Slovin technique, the data analysis technique used in this research is multiple linear regression analysis, the results of this research are that the transformational leadership Variable has a positive and significant effect on (Biznet) employees. The innovative behavior variable has a positive and significant effect on (Biznet) employees, the independent variables consisting of transformational Leadership (X_1), innovative behavior (X_2), simultaneously have a significant effect on Performance.